ANALISIS PREFERENSI KONSUMEN MINYAK GORENG KEMASAN DI GOTA MINIMARKET - Keriapy, Donny Obrial; Hendrarini, Hamidah; Tondang, Ika Sari (Universitas Galuh, 2023)
The more packaged cooking oil products that are spread and available in the market, it is not certain that there will be cooking oil products that suit the wishes and preferences of consumers. This study aims to identify consumer characteristics, determine what attributes are consumer preferences, and determine the order of attributes based on the importance of packaged cooking oil in Gota Minimarket Surabaya. The method of determining the sample using accidental sampling with a total of 100 respondents. The analytical method uses descriptive analysis for the first objective and conjoint analysis for the second and third objectives. The results showed that consumers of packaged cooking oil were dominated by women, aged 39 - 49 years, last high school education, type of work as private employee, monthly income of IDR 2,000,000 – IDR 4,000,000, monthly expenditure of IDR 2,000,000 – Rp.4,000,000, the number of family members is four, the purchase intensity is not certain, and the number of purchases is two pcs. Packaged cooking oil that is the preference of consumers at Gota Minimarket Surabaya is Sunco brand cooking oil, plastic/refill packaging, two liter size, clear clarity, golden yellow color, >1 year expiration date, complete nutritional information, as well as print media promotion. Then the order of attributes based on the level of importance of packaged cooking oil in Gota Minimarket is brand, clarity, packaging, size, color, promotion, nutritional information, expiration date.